1998
DOI: 10.1515/znb-1998-0710
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Tetramethylammonium Selenate(VI) and Chromate(VI)

Abstract: [N(CH3)4]2SeO4 and [N(CH3)4]2CrO4 have been investigated by Infrared and Raman spectroscopy, coupled thermogravimetric and differential thermal analysis combined with mass spectroscopy of the evolved gases and temperature dependent X-ray diffraction. The crystal structure of [N(CH3)4]2SeO4 has been determined from single crystal data (cubic, Fm3̄m. a -11.1077(7) Å, Z = 4) and reveals [N(CH3)4]+ cations and SeO42- anions to be arranged in a Li2O -type of structure. While the cation framework of regular tetrahed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
1
8
2
1
Order By: Relevance
“…Further, in contrast to Sato et al, they have not reported any phase change in the temperature range 130-300 K. IR and Raman studies by the same authors [4] [4]. Thus, these studies led to a controversy regarding the structure of this compound [4,5]. In the present study, we have made an attempt to resolve this.…”
Section: Introductioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Further, in contrast to Sato et al, they have not reported any phase change in the temperature range 130-300 K. IR and Raman studies by the same authors [4] [4]. Thus, these studies led to a controversy regarding the structure of this compound [4,5]. In the present study, we have made an attempt to resolve this.…”
Section: Introductioncontrasting
confidence: 54%
“…Cylindrical crystals formed upon slow evaporation of the solvent, over a few months, are dried under vacuum before using them for further studies because of their hygroscopic nature. The powder XRD measurements are carried out at room temperature using the Panalytical diffractometer and our XRD pattern compares well with that of Malchus and Jansen [4]. The compound is finely powdered and vacuum-sealed into glass ampoules of 5 mm diameter in helium atmosphere for NMR studies.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations